THE IMPACT OF PRODUCT RECOVERY ON LOGISTICS NETWORK DESIGN - FLEISCHMANN, MORITZ; BEULLENS, PATRICK; BLOEMHOF‐RUWAARD, JACQUELINE M.; VANWASSENHOVE, LUK N. (Production and Operations Management, 2001)
Efficient implementation of closed‐loop supply chains requires setting up appropriate logistics structures for the arising flows of used and recovered products. In this paper we consider logistics network design in a reverse logistics context. We present a generic facility location model and discuss differences with traditional logistics settings. Moreover, we use our model to analyze the impact of product return flows on logistics networks. We show that the influence of product recovery is very much context dependent. While product recovery may efficiently be integrated in existing logistics structures in many cases, other examples require a more comprehensive approach redesigning a company's logistics network in an integral way.